Van liefde kun je niet leven : inteviews met hoeren en hoerenjongens. - Bullinga, Marcel; Zijlsmans, Ineke; Borgers, Irma (Nijmegen : Stichting Publikaties SOF, 1982)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie